2007
DOI: 10.1007/s11199-007-9207-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Gender Role Attitudes, Role Division, and Perception of Equity among Heterosexual, Gay and Lesbian Couples

Abstract: The purpose of the present study was to investigate the relationships between gender role attitudes, household tasks, and the perception of equity among heterosexual, gay and lesbian couples. One hundred and twenty-four participants (54 heterosexuals, 30 gay men and 40 lesbians) were tested. It was found that same-sex couples had more liberal attitudes toward gender roles than did heterosexual couples. In addition, significant differences were found between the spouses in their responses regarding role divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 44 publications
4
51
0
2
Order By: Relevance
“…Previous studies have for instance found higher levels of egalitarianism among unmarried people than those who are married (Bolzendahl and Myers 2004;Fan and Marini 2000), among same-sex couples than heterosexual couples (Shechory and Ziv 2007), and in families where the wife works full-time compared to families where the wife is a full-time homemaker Myers and Booth 2002). Similarly, we found that adolescents who had working mothers or stay-home fathers held more egalitarian attitudes towards both male and female gender roles.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies have for instance found higher levels of egalitarianism among unmarried people than those who are married (Bolzendahl and Myers 2004;Fan and Marini 2000), among same-sex couples than heterosexual couples (Shechory and Ziv 2007), and in families where the wife works full-time compared to families where the wife is a full-time homemaker Myers and Booth 2002). Similarly, we found that adolescents who had working mothers or stay-home fathers held more egalitarian attitudes towards both male and female gender roles.…”
Section: Discussionsupporting
confidence: 71%
“…Research among adult couples has found gay and lesbian respondents to hold more egalitarian attitudes towards gender roles than heterosexual respondents (Shechory and Ziv 2007). Among adolescents, gender stereotyping has been found to affect gender role attitudes and sexuality in gender-specific ways.…”
Section: Dynamics Of Egalitarian Gender Role Attitudesmentioning
confidence: 99%
“…Lesbian and gay couples are also especially aware of issues regarding power and equality (e.g., Eldridge and Gilbert 1990;Reilly and Lynch 1990;Shechory and Ziv 2007). Dating scripts of lesbians and gay men reflect a lack of gender roles that appear to presage the egalitarianism of established relationships (Klinkenberg and Rose 1994).…”
Section: Evidence Of the Friendship Script In Romantic Relationshipsmentioning
confidence: 99%
“…As ideias sociais igualitárias encontram nas relações conjugais homoafetivas um terreno bastante propício à desconstrução de conceitos e padrões que geralmente estruturam as relações heteroafetivas, o que também se confirmou em outros estudos (Meletti & Scorsolini-Comin, 2015;Shechory & Ziv, 2007). São relações que subvertem mais facilmente toda a ordem social estabelecida em torno da hierarquização dos gêneros, a qual, conforme Bourdieu (1998), legitima a perpetuação da desigualdade de gênero e da "dominação masculina".…”
Section: Eu Percebo Observando As Relações Dos Meus Irmãos Héteros unclassified